Hubungan Penyesuaian Diri dan Pola Asuh Demokratis dengan Motivasi Belajar Siswa Kelas 7 Sekolah Menengah Pertama - Camelia rizkia Harahap; Saiful Akhyar Lubis; Nina Siti Salmaniah Siregar (Mahesa Research Center, 2022)
This study aims to determine the relationship between Adaptation and Democratic Parenting Patterns with Learning Motivation of Grade 7 students of SMP Shafiyyatul Amaliyyah Medan, with a population of 114 students. The research sample was 45 students. The method used in this research is quantitative method with sampling technique using purposive sampling technique. The instrument used is a Likert scale model questionnaire. The data collection technique used three scales consisting of the self-adjustment, democratic parenting and learning motivation scales. The analysis technique used is Multiple Regression. Based on the results of the study, it was concluded that: 1) Self-adjustment was positively related to student learning motivation as indicated by a correlation coefficient of R = 0.369. Where the contribution of the X1 variable to the Y variable is R2 = 13.6%. 2) Democratic parenting has a positive relationship with student learning motivation as indicated by a correlation coefficient of R = 0.302. Where the contribution of the X2 variable to Y is R2 = 9.1%. 3) Adaptation and Democratic Parenting together have a relationship with learning motivation of R = 0.434. Where the contribution of variables X1 and X2 to Y is R2 = 18.9%. From these results it can be said that the higher the self-adjustment and democratic parenting, the higher the learning motivation, and conversely the lower the self-adjustment and democratic parenting, the lower the motivation. student learning.